PENGARUH BUDAYA KERJA DAN LOYALITAS TERHADAP KINERJA GURU SD NEGERI DI KECAMATAN CIBODAS - Yanti Meitry Gunawan (Universitas Muhammadiyah Tangerang, 2018)
The The purpose of this study was to determine the influence between work culture on teacher performance, the influence between loyalty with teacher performance, and the influence between work culture and loyalty simultaneously on teacher performance. Data analysis using multiple regression analysis. Data collection is done by survey. The population and sample of the study were 47 teachers in public elementary schools in Cibodas sub-district, Tangerang city. The sampling technique used a census technique, the instrument in the study used a questionnaire. The results of the study conclude that there is an influence between work culture and teacher performance, there is a positive influence between loyalty with teacher performance, there is an influence between work culture and work discipline simultaneously on teacher work loyalty in public elementary schools in Cibodas Sub-district, Tangerang CityKeyword: work culture, loyalty, teacher performance